2022
DOI: 10.3390/cells11030319
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of FDA-Approved Drugs as a Therapeutic Approach for Niemann-Pick Disease Type C1 Using Patient-Specific iPSC-Based Model Systems

Abstract: Niemann-Pick type C1 (NP-C1) is a fatal, progressive neurodegenerative disease caused by mutations in the NPC1 gene. Mutations of NPC1 can result in a misfolded protein that is subsequently marked for proteasomal degradation. Such loss-of-function mutations lead to cholesterol accumulation in late endosomes and lysosomes. Pharmacological chaperones (PCs) are described to protect misfolded proteins from proteasomal degradation and are being discussed as a treatment strategy for NP-C1. Here, we used a combinator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…More generally, BET proteins have been shown to control lysosome- and autophagy-related genes in various cell types and disease conditions (Campbell et al, 2018; Gong et al, 2022; Jang et al, 2017; Li et al, 2020; Sakamaki et al, 2017; Segatto et al, 2020; Shen et al, 2020; Sui et al, 2019; Wakita et al, 2020). Other pathways to enhance cellular NPC1 protein levels have been explored in vitro including inhibition of histone deacetylases (Newton et al, 2017; Nunes et al, 2013; Pipalia et al, 2011; Pipalia et al, 2017; Praggastis et al, 2015; Wang et al, 2019), enhanced chaperone activity (Gelsthorpe et al, 2008; Nakasone et al, 2014; Ohgane et al, 2013; Pipalia et al, 2021; Schultz et al, 2022; Völkner et al, 2022; Wang et al, 2020; Yu et al, 2012; Zampieri et al, 2012) and reduced protein degradation (Gelsthorpe et al, 2008; Macías-Vidal et al, 2014; Nakasone et al, 2014; Zampieri et al, 2012). Similar to what we observed following JQ1 treatment, these manipulations enhanced the presence of NPC1 variants in the endosomal-lysosomal system (Gelsthorpe et al, 2008; Macías-Vidal et al, 2014; Ohgane et al, 2013; Pipalia et al, 2021; Pipalia et al, 2017; Völkner et al, 2022; Wang et al, 2019; Wang et al, 2020; Yu et al, 2012; Zampieri et al, 2012) and decreased the intracellular accumulation of unesterified cholesterol (Gelsthorpe et al, 2008; Macías-Vidal et al, 2014; Munkacsi et al, 2011; Newton et al, 2017; Ohgane et al, 2013; Pipalia et al, 2011; Pipalia et al, 2021; Pipalia et al, 2017; Praggastis et al, 2015; Völkner et al, 2022; Wang et al, 2019; Wehrmann et al, 2012; Yu et al, 2012; Zampieri et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…More generally, BET proteins have been shown to control lysosome- and autophagy-related genes in various cell types and disease conditions (Campbell et al, 2018; Gong et al, 2022; Jang et al, 2017; Li et al, 2020; Sakamaki et al, 2017; Segatto et al, 2020; Shen et al, 2020; Sui et al, 2019; Wakita et al, 2020). Other pathways to enhance cellular NPC1 protein levels have been explored in vitro including inhibition of histone deacetylases (Newton et al, 2017; Nunes et al, 2013; Pipalia et al, 2011; Pipalia et al, 2017; Praggastis et al, 2015; Wang et al, 2019), enhanced chaperone activity (Gelsthorpe et al, 2008; Nakasone et al, 2014; Ohgane et al, 2013; Pipalia et al, 2021; Schultz et al, 2022; Völkner et al, 2022; Wang et al, 2020; Yu et al, 2012; Zampieri et al, 2012) and reduced protein degradation (Gelsthorpe et al, 2008; Macías-Vidal et al, 2014; Nakasone et al, 2014; Zampieri et al, 2012). Similar to what we observed following JQ1 treatment, these manipulations enhanced the presence of NPC1 variants in the endosomal-lysosomal system (Gelsthorpe et al, 2008; Macías-Vidal et al, 2014; Ohgane et al, 2013; Pipalia et al, 2021; Pipalia et al, 2017; Völkner et al, 2022; Wang et al, 2019; Wang et al, 2020; Yu et al, 2012; Zampieri et al, 2012) and decreased the intracellular accumulation of unesterified cholesterol (Gelsthorpe et al, 2008; Macías-Vidal et al, 2014; Munkacsi et al, 2011; Newton et al, 2017; Ohgane et al, 2013; Pipalia et al, 2011; Pipalia et al, 2021; Pipalia et al, 2017; Praggastis et al, 2015; Völkner et al, 2022; Wang et al, 2019; Wehrmann et al, 2012; Yu et al, 2012; Zampieri et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…This azole derivative has been shown to bind to NPC1 in vitro and slightly improve cholesterol accumulation [39]. Also, the use of abiraterone acetate, which binds with high affinity to NPC1 in its N-terminal domain, resulted in an increase in NPC1 levels, improved co-localization in lysosomes, and a decrease in cholesterol accumulation [21]. Another therapeutic option that indirectly enhances the activity of ER-localized chaperones is the use of ryanodine receptor inhibitors, such as DHBP, which increase calcium stores in the ER by inhibiting these receptors that mediate calcium release from the ER.…”
Section: Erad Pathway and Chaperone Foldingmentioning
confidence: 99%
“…Consequently, the majority of therapies targeting NPC1 proteostasis primarily focus on improving protein folding. This includes the use of pharmacologic chaperones like abiraterone acetate, DHBP, and calnexin [21,22] or treatments aiming to modulate the expression of heat shock proteins, such as arimoclomol, JG98, AUY922, or the use of recombinant Hsp70 [23][24][25][26][27]. Changes in the mechanisms involved in the degradation pathways of proteins and other compounds due to the accumulation of cholesterol and other fatty acids in NPC have also been reported.…”
Section: Introductionmentioning
confidence: 99%
“…iPSC-derived cells decrease. 93 Ohgane et al studied the structure-activity relationship of oxysterol derivatives as pharmacological chaperones for NPC I061T mutant protein. They found that the sterol molecule without its side chain reduced its activity and affected its interaction with the NPC protein.…”
Section: Srtmentioning
confidence: 99%
“…For example, a drug called abiraterone acetate, which is used to misfold the mutant NPC1 protein, like the 25‐hydroxy cholesterol compound, restores the NPC1 protein surface inside the cell and cholesterol accumulation in NPC1 mutant cells and cells. iPSC‐derived cells decrease 93 …”
Section: Clinical Featuresmentioning
confidence: 99%